The ideal marker for measuring GFR: what are we looking for? - Maioli, Claudio; Mangano, Michela; Conte, Ferruccio; Tagliabue, Luca; Alberici, Federico; Galassi, Andrea; Cozzolino, Mario (Acta Biomedica Atenei Parmensis, 2020)
INTRODUCTION: The most accurate way of assessing kidney function is the measurement of the glomerular filtration rate (GFR). Since, we do not have good formulae to estimate GFR in elderly, in this study we  evaluate the accuracy of the most commonly used formulas for the estimation of GFR in comparison with direct measurement in elderly. MATERIALS AND METHODS: 85 patients (51 males and 34 females), with an average age of 76.2 ± 4.4 years, 42% already diagnosed with chronic kidney disease (CKD) were investigated. Two plasma samples were collected between  60-90 and 165-195 minutes after injection of 99mTc-DTPA, and the GFR was calculated applying Charles D. Russell's two-sample method. RESULTS: When comparing the GFR values obtained from the various formulae by creatinine levels with the GFR values obtained by measuring 99mTc-DTPA residue, the following concordance values emerged: (1) MDRD: 57.5 ± 9.59 %; (2) Cockroft-Gault: 48.33 ± 24.93; (3) CKD-EPI: 49.40 ± 26.30; (4) BIS1: 58 ± 6.79. CONCLUSION: Our data shows a greater concordance between the GFR values calculated with the Russell's method and the estimated values of GFR when the latter are calculated using the MDRD or BIS1 formulae.